JAVANESE MUSLIM LOCAL CULTURE AND TRADITION IN ISLAMIC PERSPECTIVE - Aqmarina Bella Agustin (Sunan Kalijaga International Journal on Islamic Educational Research, 2019)
Back to the history of Islam arrival in Java, Islam came to Java is not in the condition of cultural vacuum. There have been a growing local culture in Javanese society, like Hindu culture, Buddhist culture and Animism-Dinamism culture. This condition then makes the Javanese Muslims people can not be separated from the existing cultures, and bring some pros and cons for doing it. In terms of the said culture, it is something that is related to the cycle of life like birth, marriage, and death as a transitional phase in terms of improving religious improvement. Beyond of the said culture, there are another Javanese Muslim traditions and cultures such as Sekaten. Sekaten is a tradition that came as one of preaching’s ways to spreading Islamic beliefs in Java. Which is that time the majority was Hindu. Based on the investigation result, the existing tradition and culture (that have been) done by Javanese Muslims is the outcome of culture acculturation between Islamic and Hindu-Buddhist cultures which was done by Wali Songo (The nine-saints). Through the cultural acculturation, Walisongo spread the Islamic beliefs in wise and humanity ways. So that the Islamic beliefs can be accepted by the community as well. In Islamic perspective, doing the said tradition and culture above for the safeguard of the community united is allowed as long as the tradition and culture is not contradicting to the paramaters of Islamic beliefs it self.